Hypoxia Increases the Yield of Photoreceptors Differentiating from Mouse Embryonic Stem Cells and Improves the Modeling of Retinogenesis In Vitro123. (24th April 2013) - Garita‐HernÁndez, Marcela; Diaz‐Corrales, Francisco; Lukovic, Dunja; GonzÁlez‐Guede, Irene; Diez‐Lloret, Andrea; ValdÉs‐SÁnchez, M. Lourdes; Massalini, Simone; Erceg, Slaven; Bhattacharya, Shomi S.
Abstract: Retinitis pigmentosa (RP), a genetically heterogeneous group of diseases together with age‐related macular degeneration (AMD), are the leading causes of permanent blindness and are characterized by the progressive dysfunction and death of the light sensing photoreceptors of the retina. Due to the limited regeneration capacity of the mammalian retina, the scientific community has invested significantly in trying to obtain retinal progenitor cells from embryonic stem cells (ESC). These represent an unlimited source of retinal cells, but it has not yet been possible to achieve specific populations, such as photoreceptors, efficiently enough to allow them to be used safely in the future as cell therapy of RP or AMD. In this study, we generated a high yield of photoreceptors from directed differentiation of mouse ESC (mESC) by recapitulating crucial phases of retinal development. We present a new protocol of differentiation, involving hypoxia and taking into account extrinsic and intrinsic cues. These include niche‐specific conditions as well as the manipulation of the signaling pathways involved in retinal development. Our results show that hypoxia promotes and improves the differentiation of mESC toward photoreceptors. Different populations of retinal cells are increased in number under the hypoxic conditions applied, such as Crx‐positive cells, S‐Opsin‐positive cells, and double positive cells for Rhodopsin and Recoverin, as shown by immunofluorescence analysis. For the first time, this manuscript reports the high efficiency of differentiation in vivo and the expression of mature rod photoreceptor markers in a large number of differentiated cells, transplanted in the subretinal space of wild‐type mice. STEM CELLS 2013;31:966–978